Comparison and applicability of molecular classifications for gastric cancer. (July 2019) - Serra, O.; Galán, M.; Ginesta, M.M.; Calvo, M.; Sala, N.; Salazar, R.
Highlights: Gastric cancer management will benefit from knowledge of its molecular features. Powerful information is obtained from complementary large-scale molecular studies. Cost-effective protein and mRNA expression methods allow for GC classification. Sequencing analysis of specific GC gene panels will complement expression studies. Abstract: Gastric Cancer (GC) is a complex and heterogeneous disease, which represents a global health concern. Despite advances in prevention, diagnosis, and therapy, GC is still a leading cause of cancer-related death. Over the last decade, several clinical trials have tested novel agents for advanced GC with mostly disappointing results. Heterogeneity, the absence of molecular selection in clinical trials and powerless predictive biomarkers may be potential explanations. Different molecular classification proposals for GC based on the genetic, epigenetic, and molecular signatures have been published. Molecular characterization of GC may offer new tools for more effective therapeutic strategies, such as the development of therapies for specifically well-defined sets of patients as well as the use of new clinical trial designs, which will ultimately lead to an improvement of medical management of this disease. However, the possibilities of implementation of GC molecular classifications on daily practice and their therapeutic implications remain challenging to date. In this review, we will describe and compare these GC molecular classifications, focusing on their main characteristics as the basis for their potential therapeutic implications and strategies for their clinical application. Key Message: A better understanding of gastric cancer molecular characteristics may lead to further improvements in treatment and outcomes for patients with the disease.